Just Transition for China’s Coal Regions Towards Carbon Neutrality Targets - Ying Zhang; Dan Miao; Xiangding Hou; Mingjie Jia (Social Inclusion, 2024)
China has pledged to peak its carbon emissions before 2030 and achieve carbon neutrality by 2060. A crucial aspect of this commitment involves transitioning from coal‐dependent activities primarily concentrated in certain regions pivotal to local economies, employment, and livelihoods. High‐quality development necessitates identifying just transition strategies for these coal‐intensive regions, ensuring inclusive benefits from the energy transition. These regions exhibit disparities in economic and industrial growth, with many low‐income mining communities and inadequate public services. This calls for comprehensive policy interventions in economic, energy, societal, and environmental domains. This study aims to delineate just transition strategies for China’s coal regions, considering their unique challenges and circumstances. Initially, this article reviews the evolution of “just transition” as a concept and its policy implications. Subsequently, it explores China’s approach to achieving carbon neutrality through the lens of just transition, delving into the local economy’s reliance on coal‐related industries and the impact on employment. Following a clear delineation of the vision for just transition in China, the analysis focuses on identifying principles and pathways for transition. The goal is to propose nuanced and effective policies to ensure just outcomes in the context of China’s energy transition.